2013
DOI: 10.1073/pnas.1219756110
|View full text |Cite
|
Sign up to set email alerts
|

Trial-to-trial, uncertainty-based adjustment of decision boundaries in visual categorization

Abstract: Categorization is a cornerstone of perception and cognition. Computationally, categorization amounts to applying decision boundaries in the space of stimulus features. We designed a visual categorization task in which optimal performance requires observers to incorporate trial-to-trial knowledge of the level of sensory uncertainty when setting their decision boundaries. We found that humans and monkeys did adjust their decision boundaries from trial to trial as the level of sensory noise varied, with some subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 38 publications
6
124
1
Order By: Relevance
“…Nevertheless, in a recent study, Qamar et al (2013) found that subjects are able to incorporate trial-to-trial knowledge of different levels of sensory uncertainty when setting their decision boundaries, with some subjects even performing almost optimally. However, it is important to note that in our experiments subjects experienced two stimuli with different degrees of noise (attention) in the same trial, while in Qamar et al's experiments subjects saw a single stimulus in every trial and uncertainty changed from trial-to-trial (due to contrast variations).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in a recent study, Qamar et al (2013) found that subjects are able to incorporate trial-to-trial knowledge of different levels of sensory uncertainty when setting their decision boundaries, with some subjects even performing almost optimally. However, it is important to note that in our experiments subjects experienced two stimuli with different degrees of noise (attention) in the same trial, while in Qamar et al's experiments subjects saw a single stimulus in every trial and uncertainty changed from trial-to-trial (due to contrast variations).…”
Section: Discussionmentioning
confidence: 99%
“…While linear weighting functions can remove some redundancies, the statistics of natural images are too complex for linear models to produce completely independent responses. However, the non-linear divisive normalization model markedly reduces higher-order correlations in responses to both natural images and sounds Lyu, 2011;Sinz and Bethge, 2013), and has been shown to implement near-optimal categorization and encoding of these sensory stimuli (Qamar et al, 2013). Thus there is compelling evidence that normalization serves a specific normative role in implementing efficient information coding in sensory systems.…”
Section: Divisive Normalization In Sensory Systemsmentioning
confidence: 99%
“…Originally observed in the cortical regions of the brain involved in visual perception (Heeger, 1992), divisive normalization has now been observed in multiple forms of sensory and value processing and across species ranging from invertebrates to primates (Louie, Grattan and Glimcher, 2011;Carandini and Heeger, 2012). From a normative standpoint, divisive normalization has also been shown to yield an efficient coding of sensory information in a constrained neural system Wainwright, Schwartz and Simoncelli, 2001;Sinz and Bethge, 2013;Qamar et al, 2013). However, the normative implications for behaviour have remained unclear, particularly because divisive normalization predicts context-dependent choice behaviour that, in the absence of constraints, can be strictly termed inefficient and inconsistent (Louie, Khaw and Glimcher, 2013).…”
mentioning
confidence: 99%
“…We took inspiration from computational models of perceptual categorization (17) to estimate in choices from our Delegation task.…”
Section: Delegation Task Decision Model Descriptionmentioning
confidence: 99%
“…In order to make a decision which behavioral option is most appropriate for a given u, an optimal strategy is to compare the log-likelihood ratio of these two probability distributions (17). This computation can be expressed in terms of the probability of deferring for a given subjective value difference using the following expression ,…”
Section: Lead or Defer (Ld) Model Descriptionmentioning
confidence: 99%